Exploring the value of postmodern picture books from the perspective of creativity/character education - Kim, Kyung-Eun; Cho, Boo-Kyung (International Journal of Engineering and Technology, 2019)
This study explores the value of postmodern picture books from the viewpoint of creativity/character education. For this purpose, 164 picture books were selected. These books were analyzed based on a creativity/character criteria Â to figure out whether each book contained creativity/character elements. Furthermore, 59 books that were categorized as containing creativity/character elements were analyzed qualitatively to find the values they possessed in creativity/character education. The results were then categorized as follows: â€œAnother perspective: Wings of Sympathy and Understanding,â€ â€œStart of Exploration: Passion towards the Unknown,â€ â€œChoices and Decisions,â€ â€œThinking outside the Box: Passing my own Limitations,â€ â€œBreaking Walls and Moving towards Reconciliation and Liberty,â€ and â€œAchieving Happiness Together.â€ The results indicate the potential that postmodern picture books may have on implementing creativity/character education for children. In addition, it provides a positive outlook on educating passionate and cooperative children who do not stop at other people's judgments and predetermined stereotypes.Â Â